Optimization of construction costs and energy consumption during the operation period of residential buildings (Case study: common residential buildings in Tehran) - Meysam Zekavat; Mansoureh Tahabaz; Mohammad Reza Hafezi (تحقیقات کاربردی علوم جغرافیایی)
Buildings are one of the main pillars of economic and social development of countries that consume a large part of energy and natural resources. The purpose of writing this article is to calculate the energy consumption of a building in one year, determine the energy label and then optimize some of its features in order to reduce construction costs and reduce energy consumption of the operation phase. Is. The study area is common residential buildings in Tehran. The research method to achieve this goal is as follows: First, according to the licensing statistics of Tehran Municipality, a 5-storey southern building was selected on a land with an area of ​​320 square meters and an infrastructure of about 1100 square meters, which represents a large number of buildings in Tehran. Be. Then, by simulating the building considered in Builder Design software, the amount of gas consumption is 145.53 kWh per square meter, electricity consumption is 81.25 kWh per square meter and a total of 226.79 kWh per meter. The square was calculated per year. With this consumption, according to standard 14253, the building receives energy label C. Then, with the aim of reducing the cost of construction and energy consumption during operation, it was optimized with a genetic algorithm. Research variables, type of exterior wall (pottery or Leica), exterior (stone or brick), type of window glass (plain or low emission), type of gas between the layers of window glass (air or argon) and the ratio of the window to the south front surface (15 % -30% -45% -60%) were built. The results indicate that the best possible scenarios for the exterior facade, stone, low-emission double-glazed windows with argon gas, the outer wall of the pottery with a window-to-south front ratio of 22.5% or Leica, with a window ratio At the level of the southern front, it is 37.5%.